Parasitic subthreshold drain current and low frequency noise in GaN/AlGaN metal-oxide-semiconductor high-electron-mobility field-effect-transistors. (17th December 2020) - Takakura, K; Putcha, V; Simoen, E; Alian, A R; Peralagu, U; Waldron, N; Parvais, B; Collaert, N
Abstract: The impact of the short gate length on the drain current and low frequency (LF) noise in GaN/AlGaN metal-oxide-semiconductor high-electron-mobility field-effect-transistors has been studied. In some short devices, a parasitic subthreshold current is observed. In this article, the origin of parasitic subthreshold currents were explored using LF noise and trapping transient measurements. The LF noise power spectral density (PSD) of the devices without parasitic drain current decreased monotonically with the decrease of the drain current, while the PSD of the device with the parasitic drain current strongly increased for lower drain current. The 1/ f 1.5 noise corresponding with the parasitic leakage can be explained by the level broadening of generation-recombination centers in the GaN channel. This is confirmed by the trapping transient measurements, revealing a temperature-independent time constant, associated with the leakage path in short channel transistors, exhibiting the subthreshold humps.